2010
DOI: 10.1111/j.1365-2435.2009.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Food availability and population processes: severity of nutritional stress during reproduction predicts survival of long‐lived seabirds

Abstract: Summary1. Life-history theory predicts a trade-off between costs of current reproduction and future survival of individuals. Studies of short-lived animals in general support this prediction. However, the effect of nutritional stress during reproduction on survival of long-lived animals is poorly understood. 2. We examined the link between nutritional stress, fecundity and return to a breeding colony (hereafter 'survival') of black-legged kittiwakes (Rissa tridactyla) at two colonies with contrasting patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
163
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(172 citation statements)
references
References 75 publications
(206 reference statements)
9
163
0
Order By: Relevance
“…Our results support the flexible time budget hypothesis, with parents at both Pribilof Islands experiencing relatively poor foraging conditions, but maintaining similar chick-provisioning rates and fledging success by spending more time foraging than Bogoslof birds. However, this flexibility is not without its potential long-term costs, and high levels of CORT (Brown et al, 2005;Kitaysky et al 2007Kitaysky et al , 2010Romero and Wikelski, 2001), and increased parental effort (Golet et al, 1998) may be detrimental to adult survival. Although colony attendance differed among colonies by only 3 min h À 1 , this translates to an extra 48 min in a 16 h day diverted to foraging.…”
Section: Colony Attendancementioning
confidence: 99%
See 1 more Smart Citation
“…Our results support the flexible time budget hypothesis, with parents at both Pribilof Islands experiencing relatively poor foraging conditions, but maintaining similar chick-provisioning rates and fledging success by spending more time foraging than Bogoslof birds. However, this flexibility is not without its potential long-term costs, and high levels of CORT (Brown et al, 2005;Kitaysky et al 2007Kitaysky et al , 2010Romero and Wikelski, 2001), and increased parental effort (Golet et al, 1998) may be detrimental to adult survival. Although colony attendance differed among colonies by only 3 min h À 1 , this translates to an extra 48 min in a 16 h day diverted to foraging.…”
Section: Colony Attendancementioning
confidence: 99%
“…Levels have also been shown to be elevated during food shortages (Kitaysky et al, 1999a(Kitaysky et al, , 1999b, and in individuals in poor body condition (Kitaysky et al, 1999b;Romero and Wikelski, 2001; but see Schultner et al, 2013). Studies of seabirds have shown that the secretion of CORT is largely driven by changes in food (Benowitz-Fredericks et al, 2008;Kitaysky et al, 1999bKitaysky et al, , 2007Kitaysky et al, , 2010, and a strong negative correlation between CORT and fish abundance has been demonstrated in a number of seabird populations, including common murres (Uria aalge; Kitaysky et al, 2007). Baseline concentrations of CORT increase in a matter of days in response to food limitation 2010), and a number of seabird studies have used CORT as an index of the nutritional status of individuals (e.g., Dorresteijn et al, 2012;Satterthwaite et al, 2010;Schultner et al, 2013;Welcker et al, 2009).…”
mentioning
confidence: 99%
“…Parallel glucocorticoid and infection parameters have been measured in few studies; however, these studies have included species ranging from the seahorse (Anderson et al 2011) to amphibians (Kindermann et al 2012;Gabor et al 2013), birds (Lindström et al 2005;Kitaysky et al 2010), lizards (Oppliger et al 1998) and non-human primates Clough et al 2010), indicating the potential of this method to be used in different taxa. This approach has been applied in a small number of stress and disease studies conducted on endangered species in challenging field conditions (Aguirre et al 1995;Chapman et al 2006).…”
Section: Approaches To Understand the Relationship Between Stress Andmentioning
confidence: 99%
“…Typically, baseline corticosteronethe major glucocorticoid of birds and many other vertebrates-is elevated during the parental phase (reviewed by Romero, 2002) reflecting the increased energetic demands (and allostatic state) of parenting. As a consequence, corticosterone has frequently been considered a physiological correlate of parental resource allocation to offspring care (= parental expenditure sensu Smiseth et al, 2012; see e.g., Love et al, 2004;Kern et al, 2005;Angelier et al, 2007;Groscolas et al, 2008;Bonier et al, 2009b;Kitaysky et al, 2010;Ouyang et al, 2011;Crossin et al, 2012;Ouyang et al, 2013a;Villavicencio et al, 2014). If baseline corticosterone concentrations reflect parental expenditure, then individuals with a lower parental expenditure should express lower levels of the hormone than individuals with higher parental expenditure.…”
Section: Introductionmentioning
confidence: 99%